Optimizing Waste Banks for Effective Implementation of Waste Management Policy in Sungailiat City - Darol Arkum; Lisa Oktaviani; Meirinda, Shendy (Pencerah, 2025)
According to data from the National Waste Management Information System (SIPSN), Indonesia’s waste generation increases annually in line with population growth, with projections reaching 70.8 million tons by 2025. Waste management has therefore become a critical issue, as inadequate handling may generate significant negative impacts on both the environment and society. Previous studies indicate that the operation of Waste Banks in Sungailiat City remains suboptimal, even though these institutions play a crucial role in the success of municipal waste management. This study emphasizes the urgency of strengthening the role of Waste Banks within the formal waste management system as a strategy to optimize policy implementation. The research aims to examine how the implementation of waste management policies can be optimized through the empowerment of Waste Banks in Sungailiat City. A descriptive method with a quasi-qualitative approach was employed, using data collection techniques such as in-depth interviews, focus group discussions (FGDs), observation, documentation, and secondary data analysis of local waste management regulations. Policy implementation theory (communication, resources, bureaucracy, and disposition) was used as an analytical framework and compared against the empirical realities of Waste Bank practices in Sungailiat. The findings reveal that human resource capacity building, funding diversification, network strengthening, supportive policies with incentives, and technology utilization are key drivers for ensuring the sustainability and advancement of Waste Banks.